2020
DOI: 10.1007/s10143-020-01312-4
|View full text |Cite
|
Sign up to set email alerts
|

Adverse intraoperative events during surgical repair of ruptured cerebral aneurysms: a systematic review

Abstract: Compared with endovascular techniques, clipping of ruptured cerebral aneurysms has been shown to associate with increased morbidity in several studies. Despite this, clipping remains the preferred option for many aneurysms. The objective of this study is to describe the reported adverse events of open repair of ruptured cerebral aneurysms and their impact on patient outcome. The PubMed, Embase and Cochrane databases were searched between June 1999 and June 2019 to identify original studies of at least 100 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 58 publications
0
16
1
Order By: Relevance
“…Notably, in the literature, the most commonly reported adverse event is intraoperative rupture ( 28 ) that may reflect the binary nature of rupture, which lends itself to reporting in case series. The most-reported technical challenge of neck reconstruction/clip placement is reflected in the literature by a rate of suboptimal clip placement being recognised intraoperatively in 15.5% of cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, in the literature, the most commonly reported adverse event is intraoperative rupture ( 28 ) that may reflect the binary nature of rupture, which lends itself to reporting in case series. The most-reported technical challenge of neck reconstruction/clip placement is reflected in the literature by a rate of suboptimal clip placement being recognised intraoperatively in 15.5% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the long history of innovation in open aneurysm repair, treatment remains technically demanding with a high complication rate ( 28 ). In one series of ruptured aneurysms treated with surgical clipping, 36% of the deaths and permanent disabilities were attributed to technical intraoperative complications ( 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…Aneurysmal subarachnoid haemorrhage (SAH) is a severe disease with high morbidity and mortality 1 2. In addition to the direct injury from the bleeding, a spectrum of adverse events (AEs) may occur during the clinical course 3–6. These events can be caused by the haemorrhage itself or the clinical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…According to the recent meta-analysis, patients with HH grade I have lower risk of developing CVS [7]. In poor-grade aSAH patients urgent surgical clipping provided little benefit considering potential intraoperative injury (i.e., aneurysm rupture, difficult exposure, prolonged temporary clipping, blood loss and transfusions, and intraoperative hyper/hypotension) [8]. The new recommendation endorses endovascular coiling in the elderly, poor-grade aSAH, and aneurysms of the basilar tip [9].…”
Section: Introductionmentioning
confidence: 99%
“…Prevention and treatment of CVS remains a matter of debate. Established approaches are the administration of nimodipine initially intravenously then orally and maintenance of euvolemia, as well as treatment with hemodynamic augmentation therapy or endovascular therapy with vasodilators and angioplasty balloons [8]. A recent study also suggested the potential use of heparin [15].…”
Section: Introductionmentioning
confidence: 99%